Differences in Software Usability Level Based on User Background - Sholeh, Abdur Rohman; Fatwanto, Agung (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2023)
The development of software must consider usability as one of its key success indicators. Relatively few studies discuss the factors influencing usability, including users' backgrounds. The purpose of this research was to investigate the impact of user background, specifically gender, class (year of college admission), and frequency of use on the rating of usability. This research utilized a descriptive quantitative method with instruments: the usability matrix of the Computer System Usability Questionnaire (CSUQ), the System Usability Scale (SUS), the Usability Metric for User Experience (UMUX), and the Net Promoter Score (NPS). The research object was the Learning Management System (LMS) of two state universities in Yogyakarta. Two sets of questionnaire responses were obtained: 305 men and 442 women answered the first time, and 280 men and 584 women answered the second time. Our result shows that the mean value of usability level from CSUQ, SUS, UMUX, and NPS is mostly higher in female than male respondents, in junior to more senior students, and in respondents who use the system more frequently than those who use it less. This trend was consistent, even though the sequence of questionnaire choice order was reversed between the first and second data collection at the two universities. This research hence concluded that, based on gender, women tend to offer a higher rating of usability than men; based on class, the younger generation tends to provide higher ratings of usability than the older generation, and users who use the system more frequently tend to give higher usability rating than those who less use it.